Karaha Pujan: A Folk-Worship of Krsna in Eastern Uttar Pradesh - Dwivedi, Prabha Shankar (Religions of South Asia, 2021)
This article brings to light a kind of worship of lord Krsna practised especially by the communities of Ahir (cowherds), and Gadariya (shepherds) of eastern Uttar Pradesh, called Karaha pujan. It involves life-threatening practices performed, in a state of possession, by a bhagat, a man with charismatic authority. Besides Krsna, two forms of the goddess Sakti, namely Durga and Vansakti, are also invoked. The bhagat comes only from the Ahir or the Gadariya community. It is mostly performed under the scorching sun in summer, where the bhagat, praying to the deities, bathes in boiling hot khir (a sweet rice pudding cooked in milk), and fries puris (flat bread) dipping his hands into the boiling ghee. People come from surrounding places to witness it, feel awe for the bhagat, and believe that he is unharmed because he has been possessed by the deity or deities being worshipped. The bhagat makes predictions about the climatic conditions of the region, and about the future of the devotees, and provides solutions to their problems. This article traces similarities and parallelisms between this folk ritual performance and folk Tantric ways of worship.